Studi Eksplorasi Minat Beli Mobil Listrik pada Generasi Milenial - Adelia Nur Aprili; Andi Muhammad Sadat; Agung Kresnamurti Rivai P (Journal of Business Application, 2023)
This study aims to find out what factors that influence the purchase intention of electric vehicles on millennials in Jabodetabek and what factors contribute the most to the purchase intention. The sample and population in this study were 334 millennials in Jabodetabek using the purposive sampling method and distributing questionnaires through various social media platforms. This study uses the theory of TAM and TPB with the analytical method through Exploratory Factor Analysis (EFA) approach and linear regression analysis to process the data through SPSS 25. The result of the study found that there were nine factors that influence the purchase intention of electric cars on millennials in Jabodetabek. The ninth factor is product knowledge, perceived behavioral control, price and advertising, social influence, product perception, environmental concern, ease of use, perceived benefits, and costs. Among the nine factors, price and advertising are the factors that contribute most to the purchase intention. It is hoped that this study can be used by electric car manufacturers as a basis for developing marketing and sales strategies through consumer purchase intention.